Foodborne Outbreak Investigation in a Festival at Panchkhal Municipality of Kavrepalanchok District in Central Nepal - Adhikari, Samir Kumar; Thapaliya, Radhika; Lal, Bibek Kumar; Shrestha, Gambhir; Gautam, Dipendra; Bhattachan, Meika (Journal of Karnali Academy of Health Sciences, 2020)
Background: On September 2018, cluster of gastrointestinal cases following feast of Teej Festival was reported in Panchkhal Municipality of Kavrepalanchok, Nepal. The outbreak was investigated to identify the possible source of infection, causative agent and guide local control measures for prevention and control of the outbreak. Methods: Demographic and clinical details were collected from the cases, and the outbreak was described by time, place and person. Fourteen key informant interviews were conducted to assess the probable cause of infection, practice of food handling and preparation, source of drinking water. Semi-structured questionnaires were used to collect data from the cases. Blood examination, stool examination and culture and hepatitis serological test were done. Samples from wells and ponds were collected and microbiological tests were done in National Public Health Laboratory. Results: A total of 452 cases were identified with gastrointestinal illness and no reported deaths. All the affected population had taken food from the same place during the festival where children being more affected. Two stool samples detected Entamoeba Histolytica and some showed pus cells with no cyst or ova of organisms. Stool culture was negative. No definitive source of infection detected but was suspected to be due to improper food handling. Conclusion: This investigations confirmed the food borne outbreak in Panchkhal Municipality. The definitive causative agent of the foodborne outbreak was not identified. Proper and timely response to the outbreak is of utmost important, and can reduce the severity of the illness and halt further spread of the epidemics.